Characteristics, risk factors, and outcomes of bloodstream Candida infections in the intensive care unit: a retrospective cohort study. Issue 1 (January 2023) - Hohmann, Fábio Barlem; Chaves, Renato Carneiro de Freitas; Olivato, Guilherme Benfatti; Souza, Guilherme Martins de; Galindo, Vinicius Barbosa; Silva Jr, Moacyr; Martino, Marines Dalla Valle; Menezes, Fernando Gatti de; Corrêa, Thiago Domingos
Objective: The main objective was to assess the clinical characteristics, associated factors, and outcomes of patients admitted to the ICU for candidemia. The secondary objective was to examine the relationship of candidemia with the length of stay and mortality. Methods: The analysis was a retrospective single-center cohort study addressing the effect of invasive candidemia on outcomes. This study was performed in a medical-surgical ICU located in a tertiary private hospital in São Paulo, Brazil. Data was collected through the review of the hospital database. Results: In total, 18, 442 patients were included in our study, including 22 patients with candidemia. The median age was similar in patients with and without candidemia [67 (56–84) vs. 67 (51–80)]. Most patients were male, and the proportion of men was higher among patients with candidemia (77% vs. 55.3%). The rates of renal replacement therapy (40.9% vs. 3.3%), mechanical ventilation (63.6% vs. 29.6%), and parenteral nutrition (40.9% vs. 4.8%) were higher in patients with candidemia than in those without candidemia. The mortality rate (77.3% vs. 11.9%) and length of hospital stay [42 days (23.0–78.8) vs. 8 days (5.0–17.0)] were significantly higher in patients with candidemia. Conclusions: Patients with candidemia are prone to longer hospital stay and mortality. In addition, we found associations of candidemia with the use of invasive mechanical ventilation, renal replacement therapy, and parenteral nutrition.